Energy and the evolution of farming systems. The potential of mixed farming in the moist savannah of sub-Saharan Africa - Jabbar, M.A. (1996)
The moist savannah zone in sub-Saharan Africa is regarded as a high potential area for crop and livestock production. Currently, human labour is the principal source of power for crop production and the level of commercial energy use is very low. Agropastoralism and pastoralism are the principal methods of livestock production. Crop-livestock mixed farming, in which manure and animal power are important energy sources in the production process, is only now emerging. The integration of crops and livestock and the implications for agricultural energy sources are related to population pressure and labour intensity, the intensification of crop production with and without livestock, the role of traction in general and in specific niches, the contribution of livestock to the development process in terms of food or other inputs, and the role of public policy and intervention in development. The principal objective of this paper is to establish the relationship between energy and the evolution of farming systems, to assess how the increased agricultural energy needed in the moist Savannah region may be generated and particularly to assess the potential for development of mixed farming and its role in meeting future energy needs.